(untitled) (Journal of Dhaka Medical College, 2024)
Background: The novel corona virus disease 2019 (COVID-19) is major public health issue. It is the most significant global health challenge in the world. Biomarkers play a significant role to detect the severity of COVID-19 infection in the perspective of management of the patients. Aim and objective: We aimed to assess the association between the levels of C-Reactive Protein and D-dimer in COVID-19 patients. Methods: This cross-sectional study was conducted in the department of Pathology and department of Microbiology GMCH, Khulna. 152 patients with SARS-CoV-2 (COVID -19) positive patients were enrolled in this study. C-reactive protein and D-dimer levels are measured in the laboratory of Pathology department, GMCH, Khulna. All statistical computations were performed by using window-based computer software devised with Statistical Packages for Social Sciences (IBM SPSS Statistics 21 version). Results: In this study CRP level was found of mean value of 62.84± 44.64 mg/L with a range of 1.40-195.20 mg/L. It was normal in 21 (13.8%) patients and increased in in 131 patients (86.2 %). The mean value of D-dimer was 2.48 ± 02.20 mg/L with a range of 0.10-9.35 mg/L. D-dimer was normal in 26 (17.1%) patients, whereas it was increased in 126 patients (82.9 %). We performed Pearson’s correlation-coefficient (r) test to compare the association between the levels of CRP with D-dimer in COVID-19 positive patients. There was moderately positive and significant correlation (r = +0.647, p <0.05) between the levels of CRP and D-dimer. Conclusion: There was statistically significant correlation between the levels of serum CRP with D-dimer in COVID-19 positive patients. These two biomarkers can be used to assess the severity in patients with COVID-19 positive with thrombotic disorder for reduction of morbidity and mortality of COVID positive patients. J Dhaka Med Coll. 2023; 32(1) : 57-62